Desain dan Analisa Ekonomi PLTS Atap untuk Villa di Bali - Sumariana, Kadek; Kumara, I Nyoman Satya; Ariastina, Wayan Gede (Majalah Ilmiah Teknologi Elektro; Vol 18 No 3 (2019): (September - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2019.v18i03.P06, 2019)
Abstract —Bali province is one of 34 provinces of Indonesia and according to General Plan of National Energy it was expected to develop around 110 MW solar PV by 2025. Economically, Bali is considered as the center of Indonesian tourism industry. A wide range of accommodations have been developed to support the industry including villa. In this paper, potential of rooftop PV of villas in Bali is presented. Rooftop PV capacity was designed with objective to meet 23% of the villa’s energy consumption. Two villas in the southern of Bali were taken as examples. Energy audit was conducted to study the energy usage of both villas. Based on the design objective, 13,7 kWp grid-connected PV was proposed for each of the villa. With these results, it was projected that all villas in Bali could add solar PV capacity around 34,8 MWp which canpotentialy generateannual energy of 54.741 MWh. Investment analysis and environmental performance are also included on this paper. The results presented here will help provincial and district governments of Bali to get insight into potential of tourism sector to support PV development and subsequentlyto developappropriate policies and regulations to accelerate the uptake of rooftop PV in Bali.